Changes in Mass Residence Building Designs Based on The Needs of Property Owners - Abdullah Hibrawan; Imaniar Sofia Asharhani; Daniel Fernando (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2024)
Many property developers in Indonesia impose strict provisions regarding changes or developments to initial building designs, often forcing property owners to hire an architect to renovate their buildings to comply the changes with the applicable property developer regulations. By conducting research using a survey method of mass residential property owners, it is hoped that we will be able to find out what changes are needed when the building is renovated. Aspects considered in this research include: space requirements, room size and building material changes. After conducting this research, it can be concluded that changes and/or development of building designs are most often requested or required by mass residential property owners, which of course do not violate the provisions of the property developer. In this way, it is hoped that property developers can find out the latest design trends as alternative building designs in the future.